2007
DOI: 10.1158/0008-5472.can-06-4628
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Nicotinic Acetylcholine Receptor Subunit Genes in Non–Small-Cell Lung Cancer Reveals Differences between Smokers and Nonsmokers

Abstract: Nicotine and its derivatives, by binding to nicotinic acetylcholine receptors (nAChR) on bronchial epithelial cells, can regulate cellular proliferation and apoptosis via activating the Akt pathway. Delineation of nAChR subtypes in non-small-cell lung cancers (NSCLC) may provide information for prevention or therapeutic targeting. Expression of nAChR subunit genes in 66 resected primary NSCLCs, 7 histologically non-involved lung tissues, 13 NSCLC cell lines, and 6 human bronchial epithelial cell lines (HBEC) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
151
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(159 citation statements)
references
References 50 publications
7
151
0
Order By: Relevance
“…These nAChR receptors are expressed in human and rodent bronchial epithelial cells, 104 and in non-small-cell lung cancers. 105 We do not know at this time whether polymorphisms in this cluster can directly increase the sensitivity of the target tissues to tobacco smoke and/or nicotine toxicity. 106 Besides the option that variants in the CHRNA5-CHRNA3-CHRNB4 loci increase LC risk solely due to involvement in increased smoking, it is also possible that genetic variants in nAChRs directly influence mechanisms of lung carcinogenesis, without mediation by smoking phenotypes.…”
Section: Chrna5-chrna3-chrnb4 and Lcmentioning
confidence: 99%
“…These nAChR receptors are expressed in human and rodent bronchial epithelial cells, 104 and in non-small-cell lung cancers. 105 We do not know at this time whether polymorphisms in this cluster can directly increase the sensitivity of the target tissues to tobacco smoke and/or nicotine toxicity. 106 Besides the option that variants in the CHRNA5-CHRNA3-CHRNB4 loci increase LC risk solely due to involvement in increased smoking, it is also possible that genetic variants in nAChRs directly influence mechanisms of lung carcinogenesis, without mediation by smoking phenotypes.…”
Section: Chrna5-chrna3-chrnb4 and Lcmentioning
confidence: 99%
“…Athymic nude mice tumorxenograft experiments with subcutaneous Hep3B tumor confirmed its in vivo antitumor activity for abolishing the growth of the tumor at a dose of 10 mg/kg/day on day 9 when administrated intraperitoneally with no observable toxicity from the vital organs at histological level. To identify the most involved molecular pathways of the drug actions, a preliminary cDNA microarray analysis was performed in the Genome Research Centre of the University of Hong Kong using the Human Genome U133 Plus 2.0 arrays (Affymetrix) as previously described 28 to identify the differentially expressed genes in cancer cells after the treatment with compound 3. Total RNA was extracted from the vehicle control and the esophageal cancer cell line KYSE150 treated with 8.5 μg/mL of compound 3 for 48 h with reference to the MTS 50 value (6.25− 12.5 μg/mL).…”
mentioning
confidence: 99%
“…Indeed, EGFR overexpression is observed in 62% of NSCLC cases and is correlated with poor prognosis (21,38,54). Studies in recent years have also shown polymorphisms in nAChR genes that correlate with NSCLC in smokers (25,37,51). Since primary cells from the lung as well as lung cancer cells can proliferate in response to both nAChR and EGFR signaling, it is probable that there might be common mediators of these signals in smokers and nonsmokers.…”
mentioning
confidence: 99%